Assessing the Effectiveness of the Posyandu Program on Maternal and Child Health Outcomes in Kekalik Jaya and Child Health - Masriawan, Junaidi; Ariadi, Zulhan (Lembaga Publikasi Ilmiah Nusantara, 2025)
Background: The Integrated Health Post (Posyandu) is a community-based program in Indonesia aimed at improving maternal and child health outcomes through routine monitoring, education, and access to basic services. In Kekalik Jaya, Posyandu plays a crucial role in early detection of stunting, immunization coverage, and maternal nutrition monitoring. Yet the effectiveness of these interventions in local contexts often depends on implementation quality and community engagement.Objective: This study aims to assess the effectiveness of the Posyandu program in Kekalik Jaya on maternal health indicators (antenatal care visits, maternal nutritional status) and child health outcomes (immunization completeness, growth monitoring, stunting prevalence).Methods: This qualitative descriptive literature review synthesizes research and documents from academic journals, reports, and proceedings accessed via Google Scholar. Thematic content analysis was employed to identify patterns, mechanisms, and outcomes tied to Posyandu activities.Results: Findings highlight how the Posyandu model facilitates community engagement, health education, and early screening. Positive effects include increased antenatal care uptake, improved exclusive breastfeeding rates, better immunization coverage, and reductions in stunting incidence. Implementation strategies such as participatory cadre training, home visit tracking, and integration of digital recording systems emerged as critical.Conclusion: The Posyandu program serves as an effective sociomedical intervention bridging service provision and community empowerment. Its success in Kekalik Jaya underscores the importance of context-specific design, cadre capacity, and sustained support mechanisms for maternal and child health improvement.